(untitled) (Al-Academy, 2025)
The topic is based on the plastic concept and the creation of plastic images and introducing them into the theater through the visual sign of the formation or by dealing with sculptural methods and producing the motor and artistic performance in accordance with the sculptural foundations that the director addressed and the foundations of his artistic image in this way, and clarifying the applied methods that were used in applying this concept in the show. Theatrical and directing mechanisms that directors dealt with in forming the aesthetic and artistic formation of the plastic unit from a philosophical standpoint to form the directing style